2017
DOI: 10.2807/1560-7917.es.2017.22.8.30467
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years and counting: epidemiology of an outbreak of isoniazid-resistant tuberculosis in England and Wales, 1995 to 2014

Abstract: An outbreak of isoniazid-resistant tuberculosis first identified in London has now been ongoing for 20 years, making it the largest drug-resistant outbreak of tuberculosis documented to date worldwide. We identified culture-confirmed cases with indistinguishable molecular strain types and extracted demographic, clinical, microbiological and social risk factor data from surveillance systems. We summarised changes over time and used kernel-density estimation and k-function analysis to assess geographic clusterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…TB disproportionately affects different segments of the population. Higher male-to-female ratio was reported in some studies and surveillance data as well as higher TB notification rate and lower mortality rate among males [1,5,6]. Changes in the occurrence of the disease by age, sex, education, anatomical site of the disease, history of previous treatment, HIV status and drug resistance are also important indicators of TB control programmes [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…TB disproportionately affects different segments of the population. Higher male-to-female ratio was reported in some studies and surveillance data as well as higher TB notification rate and lower mortality rate among males [1,5,6]. Changes in the occurrence of the disease by age, sex, education, anatomical site of the disease, history of previous treatment, HIV status and drug resistance are also important indicators of TB control programmes [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…5 Multiple molecular epidemiologic studies show that DR-TB strains can be transmitted and that clusters of resistant strains can persist over long periods. [25][26][27][28] However, previous molecular epidemiologic studies have reached different conclusions; some have found that DR strains are more likely to be clustered than DS strains while others have shown the reverse. [29][30][31] Some studies have suggested that the association with clustering depends on the specific drug resistance phenotype and/or mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to anti‐TB drugs is a complex phenomenon that depends on a wide range of factors, including structural sociodemographic factors (poverty, gender and discrimination), patient‐related factors (motivation, knowledge, beliefs and attitudes) and social context and health service factors (Munro et al., ; Smith et al., ; Woith & Larson, ). For instance, in children, adherence depends on the motivation of the parents, while adherence to any chronic medication becomes more challenging during adolescence (Chang, Eitzman, Nahid, & Finelli, ).…”
Section: Introductionmentioning
confidence: 99%